1998
DOI: 10.1097/00006123-199808000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Natural History of Cerebral Venous Malformations

Abstract: The hemorrhage rate of a patient with venous malformations is similar to the rates presented in previous reports for patients with cavernous malformations without previous symptomatic hemorrhage. We think that hemorrhage in a patient with venous malformations may be related to an underlying but not yet documented cavernous malformation. Because of the low risk for new neurological events, we advocate conservative management. The risks associated with surgical intervention greatly exceed the low risk of morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(101 citation statements)
references
References 38 publications
1
96
1
3
Order By: Relevance
“…54 On angiograms they appear as radially arranged medullary veins with a central draining trunk, an abnor mality of cerebral surface veins, and a "star cluster" ap pearance of draining veins. 46 Although, they have been reported to be associated with intracranial hemorrhage, seizures, and progressive neurological defects, the risk of significant hemorrhage is negligible (0.22-0.68%), 18,20,43,50 and current recommendations strongly suggest conserva tive management of these lesions. 28 With the widespread availability of MR imaging, DVAs are frequently encoun tered in association with other vascular malformations particularly CMs and less commonly parenchymal AVMs and capillary telangiectasia.…”
Section: Developmental Venous Anomaliesmentioning
confidence: 99%
“…54 On angiograms they appear as radially arranged medullary veins with a central draining trunk, an abnor mality of cerebral surface veins, and a "star cluster" ap pearance of draining veins. 46 Although, they have been reported to be associated with intracranial hemorrhage, seizures, and progressive neurological defects, the risk of significant hemorrhage is negligible (0.22-0.68%), 18,20,43,50 and current recommendations strongly suggest conserva tive management of these lesions. 28 With the widespread availability of MR imaging, DVAs are frequently encoun tered in association with other vascular malformations particularly CMs and less commonly parenchymal AVMs and capillary telangiectasia.…”
Section: Developmental Venous Anomaliesmentioning
confidence: 99%
“…However, as implied by its name, DVA constitutes a venous deviation and inevitably a decreased flexibility for the territorial drainage is expected. Cases like cerebral infarction and secondary hemorrhage as a result of venous thrombosis of a DVA have been reported 15 . Intracranial hemorrhage as a result of DVA associated with AVM was, however, rarely discussed in the literature.…”
Section: A B D C F Ementioning
confidence: 99%
“…[35,[38][39][40] Prospective studies on venous angiomas have demonstrated a very low rate of both symptomatic hemorrhage (0.34% per year) and neurologic symptoms; bleeding, when it rarely occurs, has been hypothetically blamed on putative neighboring cavernous malformations. [41] Blood flow through venous angiomas is low, and they are thought to drain normally from the brain.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Although cases of existence of DVAs and seizures have been reported, the correlation between them has not been firmly determined. [15,22,38,41,45] The study of Striano et al [15] revealed that DVAs are rarely found in epileptic patients, as distinct from other vascular malformations, cavernomas in particular. Topographic and/or etiological relationships between DVA and epilepsy are still undefined.…”
Section: Discussionmentioning
confidence: 99%